EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN EVERYONE IS A TEACHER HERE DAN THINK PAIR SHARE PADA MATERI KPK DAN FPB DITINJAU DARI MOTIVASI BELAJAR SISWA - Nur Anida Laila; Tri Atmojo Kusmayadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aims of this research were to determine:  (1) which had better learning achievement among students taught by using learning model Think Pair Share with Everyone is a Teacher Here (TPS  with ETH), Think Pair Share (TPS), or direct instruction, (2) which had  better learning achievement, students with motivation level of high, medium, or low (3) at each of the learning model, which had better learning achievement, students with motivation level of high, medium, or low,  (4) at each of the motivation level, which had better learning achievement among students who taught by using learning model TPS with ETH with TPS, or direct intruction.  Based on the test hypothesis, it could be concluded as follows. (1) Cooperative learning  model TPS with ETH produces learning achievement better than the model of TPS and direct learning. TPS learning produces better achievement than direct learning models. (2) The mathematics learning achievement of students with high motivation is better than those with moderate and low motivation. The mathematics learning achievement of students with moderate motivation is better than those with low motivation. (3) At the TPS with ETH learning and direct instruction, the mathematics learning achievement of students with high motivation is as same as those with moderate motivation. Similarly, mathematics learning achievement of students with moderate motivation is as same as those with low motivation. While in the case of the TPS learning, the learning achievement of students with high motivation is as same as those with moderate motivation. Similarly, the mathematics achievement of students with the moderate motivation is the same as students with low motivation. However, the mathematics achievement of students with high motivation is better than thoese with low motivation. (4) For students with high and moderate motivation, the learning achievement of students taught with TPS learning with ETH is the same as those with those taught with merely TPS and direct learning. In the other hand TPS with ETH gives good impsct to the learning achievement than direct learning.  On the case of student’s low motivation TPS with ETH shows that the use two of the method gives good impact in the same with the student treated with TPS or direct learning.Keywords: TPS with ETH, TPS, direct learning, and Student’s Learning Motivation